Pendidikan Etika Bagi Siswa Dalam Mengunakan Media Sosial - Norianti Pai Tiba; Pe Demas Haba Ratu; Yitra Gloria Bana; Selviana Ambu Kaka; Merti Tana; Chors Putra Mardanil Tabun; Maya NovitaMbura; Ruben Dala Wunu (Educational Journal, 2026)
The development of digital technology and social media has brought significant changes to the lives of the younger generation, especially students. However, a lack of understanding of ethical social media use often leads to problems such as the spread of hate speech, defamation, and digital addiction. This study aims to analyze the factors contributing to students' lack of ethical behavior in using social media, explain the role of ethics education in shaping student behavior, and determine the effect of ethics education on students' ability to filter information and avoid the spread of hoaxes. The research method used a literature review by analyzing theories and relating them to the context of student education in the digital era. The results show that ethics education plays a central role in shaping students' behavior with integrity, empathy, and respect for differences in the virtual world. Ethics education also influences students' habits in filtering information and avoiding the spread of hoaxes. Thus, ethics education is a key foundation in developing an  intelligent and moral digital generation.